Influence of lightning strikes on the structural performance of Ni-glass/epoxy radar-absorbing structures. (1st August 2020) - Jang, Min-Su; Choi, Jae-Hun; Jang, Woo-Hyeok; Nam, Young-Woo; Kim, Chun-Gon
Abstract: This study presents a quantitative evaluation of the structural impact of lightning strikes on glass/epoxy and Ni-glass/epoxy composites used in radar-absorbing structures (RAS), as well as the actual design of a 5-slab RAS. Image processing was utilized to evaluate the fiber and resin in the damaged area caused by lightning. The decrease in mechanical properties due to lightning strikes were evaluated by compression-after-lightning tests. As a result, penetration failures were observed when current flowed in the thickness direction in the dielectric composites and the 5-slab radar-absorbing structure. This penetration failure resulted in greater than 50% reduction of the residual compressive strength because the damage was distributed throughout the entire specimen thickness, even at low energy current intensities (0–30 kA). Therefore, considering application systems, it is necessary to design lightning protection systems to prevent penetration failure in order to apply radar-absorbing structures to actual aircraft structures.